Prognostic implications of obstructive sleep apnea in patients with acute coronary syndrome stratified by homocysteine level: a prospective cohort study - Xiuhuan Chen; Lei Zhen; Hui Ai; Bin Que; Jingyao Fan; Xiao Wang; Yan Yan; Siyi Li; Zekun Zhang; Yun Zhou; Wei Gong; Shaoping Nie (Respiratory Research, 2023)
Abstract Background Sporadic studies have examined the impact of OSA on ACS patients by homocysteine (Hcy) level. This study attempted to comprehensively evaluate the effects of the interaction between Hcy and OSA on long-term cardiovascular outcomes in ACS patients. Methods In this prospective, large-scale cohort study, 2160 patients admitted for ACS were recruited to undergo overnight sleep monitoring. OSA was diagnosed when apnea–hypopnea index ≥ 15 events/h. Patients with normohomocysteinemia (NHcy) were defined as having serum Hcy ≤ 15 μmol/L, and the others had hyperhomocysteinemia (HHcy). The primary endpoint was major adverse cerebrocardiovascular event (MACCE), a composite of cardiovascular death, myocardial infarction, stroke, ischemia-driven revascularization and hospitalization for unstable angina and heart failure. Results A total of 1553 eligible ACS patients (average age: 56.3 ± 10.5 years) were enrolled, among which 819 (52.7%) had OSA, and 988 (63.6%) were with NHcy. OSA did not significantly affect the level of Hcy. During a median follow-up of 2.9 (1.6, 3.5) years, after adjustment for clinical confounders, OSA was associated with increased risk for MACCE occurrence versus non-OSA ones in ACS patients with NHcy (adjusted hazard ratio [HR] = 1.36, 95% confidence interval [CI] 1.02–1.83, P = 0.039), but not in those with HHcy (adjusted HR = 0.92, 95%CI 0.62–1.36, P = 0.668). There was an absence of interaction between homocysteine level and OSA in relation to MACCE (interaction P = 0.106). Conclusions OSA was independently associated with worse prognosis in ACS patients with NHcy. Our study emphasized the necessity to identify potential presence of OSA in such a population. Trial registration: ClinicalTrials.gov; Number: NCT03362385; URL: www.clinicaltrials.gov .